Psychological Support System for Hospital Workers During the Covid-19 Outbreak: Rapid Design and Implementation of the Covid-Psy Hotline - Geoffroy, Pierre A.; Le Goanvic, Véronique; Sabbagh, Olivier; Richoux, Charlotte; Weinstein, Aviv; Dufayet, Geoffrey; Lejoyeux, Michel (Frontiers in Psychiatry, 2020)
Background The worldwide coronavirus outbreak has put hospital workers under extreme stress with possible mental health problems. In this context, we decided to rapidly design and implement a psychological support system for all hospital workers in Paris during the Covid-19 outbreak. Methods We built a hotline in 3 days using the following steps: 1) official mandate, 2) request for the creation of hotline numbers, 3) formulation of psychological intervention materials and policies, 4) call for volunteer certified psychologists, 5) call for volunteer certified psychiatrists in case of psychiatric cases, 6) creation of an anonymous and protected database, and 7) communication and regular reminders about the existence of the hotline for hospital workers. Results After the first 26 days, we received 149 calls with a mean of 5.73 calls/day (SD=3.22). The average call duration was 18.5 min (min=1; max=65min; SD=14.7), and mostly women (86%) called. The mean age was 32.7 years old (SD=11.0). Calls from hospital workers were from all professions; though mostly represented by frontline healthcare workers, non-frontline departments also called (total of 44 departments). Reasons for calling were anxiety symptoms (n=73, 49%), request for hotline information (n=31, 20.8%), worries about Covid-19 (n=23, 15.44%), exhaustion (n=17, 11.41%), trauma reactivation (n=10, 6.11%), insomnia (n=9, 6.0%), anger (n=8, 5.37%), depressive (n=6, 4.02%), and psychotic symptoms (n=3, 2.01%). Regarding referrals, 105 (70.47%) of them were referred to psychosocial, Covid, and general support. Conclusions This psychological support system can be easily duplicated and seems to benefit all hospital professions that all appeared psychologically affected.